2019
DOI: 10.1038/s41586-019-1054-1
|View full text |Cite
|
Sign up to set email alerts
|

CAR T cell trogocytosis and cooperative killing regulate tumour antigen escape

Abstract: Chimeric antigen receptors (CARs) are synthetic antigen receptors that reprogram T cell specificity, function and persistence1. Patient-derived CAR T cells have demonstrated remarkable efficacy against a range of B-cell malignancies1–3, and the results of early clinical trials suggest activity in multiple myeloma4. Despite high complete response rates, relapses occur in a large fraction of patients; some of these are antigen-negative and others are antigen-low1,2,4–9. Unlike the mechanisms that result in compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
400
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(476 citation statements)
references
References 23 publications
20
400
1
Order By: Relevance
“…Further characterization of CAR Tregs in mice in which they were detectable on day 7 after injection also revealed variation in the maintenance of the expected FOXP3 + phenotype, with the CD28wt-CAR Tregs having the most consistent and high proportion of FOXP3expressing cells (Figure 2F, Supplemental Figure 4C). It has been reported that one property of CAR Tconv is their ability to acquire their target antigen through a process called trogocytosis (Hamieh et al, 2019). In all samples where Myc+ CAR T cells were detected, none were HLA-A2+, suggesting that at least in this model and at this time point, we were not able to detect trogocytosis (Supplemental Figure 4D).…”
Section: Wild Type Cd28 Signaling Is Required For Optimal Treg Supprementioning
confidence: 67%
“…Further characterization of CAR Tregs in mice in which they were detectable on day 7 after injection also revealed variation in the maintenance of the expected FOXP3 + phenotype, with the CD28wt-CAR Tregs having the most consistent and high proportion of FOXP3expressing cells (Figure 2F, Supplemental Figure 4C). It has been reported that one property of CAR Tconv is their ability to acquire their target antigen through a process called trogocytosis (Hamieh et al, 2019). In all samples where Myc+ CAR T cells were detected, none were HLA-A2+, suggesting that at least in this model and at this time point, we were not able to detect trogocytosis (Supplemental Figure 4D).…”
Section: Wild Type Cd28 Signaling Is Required For Optimal Treg Supprementioning
confidence: 67%
“…Moreover, cancer cells using intercellular transfer of cell‐surface proteins also play critical roles in re‐shaping the tumor microenvironment to support their expansion and metastatic activity, as well as dampen antitumor immune responses . In this context, a recent study by Hamieh et al . revealed that both CD19 and CD22 expressed on NALM6 acute lymphoblastic leukaemia cells could be transferred to chimeric antigen receptor (CAR)‐T cells through the process of trogocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cancer cells using intercellular transfer of cell-surface proteins also play critical roles in re-shaping the tumor microenvironment to support their expansion and metastatic activity, as well as dampen antitumor immune responses. 15,16 In this context, a recent study by Hamieh et al 17 revealed that both CD19 and CD22 expressed on NALM6 acute lymphoblastic leukaemia cells could be transferred to chimeric antigen receptor (CAR)-T cells through the process of trogocytosis. Consequently, the density of the target molecules CD19 and CD22 was decreased on the tumor cells, and the T-cell killing activity was abated by the fratricide and exhaustion of the T cells with molecules acquired target by trogocytosis by CAR-T cells.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism may be due to the expansion of a small subset of CD19-negative cancer cells or alternatively, the cells may downregulate CD19 from the cell surface in order to evade detection by CAR T cells, rendering them resistant [19,21,[34][35][36][37]. Additionally, it was recently shown that a phenomenon referred to as trogocytosis is a mechanism of antigen escape whereby the antigen is transferred to the CAR T cell [38]. It has also been shown that transduction of a single leukemic blast with an anti-CD19 CAR that was re-infused into a B-ALL patient, ultimately resulted in relapse and death of the patient [39].…”
Section: Car T Cell Therapymentioning
confidence: 99%